Effect of dietary supplementation of chromium on growth and biochemical parameters of Labeo rohita (Hamilton) fingerlings - Giri, Abhay Kumar; Prasad Sahu, Narottam; Saharan, Neelam; Dash, Gyanaranjan (Indian Journal of Fisheries, 2014)
A 60-day feeding experiment was conducted to evaluate the effect of dietary chromium on growth, feed efficiency and biochemical parameters of Labeo rohita fingerlings. Four isonitogenous (crude protein 35%) and isocaloric (415 k cal 100 g-1) experimental feeds were prepared by supplementing different levels of dietary chromium picolinate viz., control (0.0 mg kg-1), T1 (0.4 mg kg-1), T2 (0.8 mg kg-1) and T3 (1.2 mg kg-1). Weight gain WG (%), specific growth rate (SGR), feed efficiency ratio (FER) and protein efficiency ratio (PER) and apparent net protein utilisation (ANPU %) were significantly improved (p